Assessing neurosurgical non‐technical skills: an exploratory study of a new behavioural marker system. Issue 5 (5th May 2014) - Michinov, Estelle; Jamet, Eric; Dodeler, Virginie; Haegelen, Claire; Jannin, Pierre
Abstract Rationale, aims and objectives The management of non‐technical skills is a major factor affecting teamwork quality and patient safety. This article presents a behavioural marker system for assessing neurosurgical non‐technical skills (BMS‐NNTS). We tested the BMS during deep brain stimulation surgery. Method We developed the BMS in three stages. First, we drew up a provisional assessment tool based on the literature and observation tools developed for other surgical specialties. We then analysed videos made in an operating room (OR) during deep brain stimulation operations in order to ensure there were no significant omissions from the skills list. Finally, we used five videos of operations to identify the behavioural markers of non‐technical skills in verbal communications. Results Analyses of more than six hours of observations revealed 3515 behaviours from which we determined the neurosurgeon's non‐technical skills behaviour pattern. The neurosurgeon frequently engaged in explicit coordination, situation awareness and leadership behaviours. In addition, the neurosurgeon's behaviours differed according to the stage of the operation and the OR staff members with whom she was communicating. Conclusions Our behavioural marker system provides a structured approach to assessing non‐technical skills in the field of neurosurgery. It can also be transferred to other surgical specialties and used in surgeon training curricula.